Analisis Pengaruh Jumlah Kredit, Modal, dan Partisipasi Masyarakat Terhadap Pendapatan LPD di Kecamatan Abang Periode 2018-2022 - Ni Kadek Adi Sugiantari; Made Endra Kartika Yudha (Journal Of Business, Finance, and Economics (JBFE), 2024)
In 2018, the number of Village Credit Institutions (LPD) that ceased operations in Abang District increased, with 5 LPDs declared non-operational. Additionally, unhealthy practices in LPD management were found in Abang District, specifically in Sega Village, where the Head of the LPD of Sega Traditional Village embezzled customer funds amounting to Rp 548,510,000. This corruption case was revealed through an audit conducted by the Village Credit Institution Empowerment Agency (LPLPD) of Abang District (Nusabali.com, accessed on December 14, 2023). This study aims to analyze the influence of loan amount, capital, and community participation on the income of LPDs in Abang District for the 2018-2022 period. The research design used is a quantitative associative approach, as the data is presented in numerical form, and statistical analysis is employed for data processing. The study uses panel data regression analysis to assess how independent variables such as loan amount, capital, and community participation affect the dependent variable, which is income. The sampling technique applied is saturation sampling, where the entire population is used as the sample. The results of the study indicate that the loan amount has a positive and significant effect on LPD income in Abang District for the 2018-2022 period; capital has a positive and significant effect on LPD income in Abang District for the same period; community participation has a positive but not significant effect on LPD income in Abang District for the 2018-2022 period. Collectively, the variables of loan amount, capital, and community participation simultaneously affect LPD income in Abang District for the 2018-2022 period.